2015
DOI: 10.1038/nature14967
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping tree density at a global scale

Abstract: The global extent and distribution of forest trees is central to our understanding of the terrestrial biosphere. We provide the first spatially continuous map of forest tree density at a global scale. This map reveals that the global number of trees is approximately 3.04 trillion, an order of magnitude higher than the previous estimate. Of these trees, approximately 1.39 trillion exist in tropical and subtropical forests, with 0.74 trillion in boreal regions and 0.61 trillion in temperate regions. Biome-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
488
2
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 758 publications
(520 citation statements)
references
References 31 publications
13
488
2
17
Order By: Relevance
“…Although a decease was detected, it remains relatively high in coverage. For the area whose crown cover fluctuates, additional research is suggested on the driving factor for the variation in forest cover, as is presented by Crowther et al [53]. …”
Section: Forest Cover Changementioning
confidence: 99%
“…Although a decease was detected, it remains relatively high in coverage. For the area whose crown cover fluctuates, additional research is suggested on the driving factor for the variation in forest cover, as is presented by Crowther et al [53]. …”
Section: Forest Cover Changementioning
confidence: 99%
“…systems genetics | lignocellulosic biomass | cell wall | bioenergy | network-based data integration W ood (secondary xylem tissue) from trees represents a significant proportion of global carbon sequestration (1,2), while also providing raw materials, be it in the form of timber, paper, or other biomaterials and value-added derivatives, such as cellulose (3) and lignin (4). Fast-growing trees such as poplars and eucalypts with short rotation times, small genome sizes (500-600 Mbp), large genetic diversity, and established breeding populations are widely cultivated as woody biomass crops and are well suited for biotechnological improvement (5)(6)(7)(8).…”
mentioning
confidence: 99%
“…A credible estimate of the current forest condition and ongoing dynamics is a basis for reliable forecasts of the global changes and sustainable forest management. Nowadays the most worldwide common approach for assessment of forest conditions and dynamics is based on the systematic ground-based forest monitoring, performed at a set of regularly structured locations (Ferretti 2013;Crowther et al 2015). In Europe, one of the most ambitious projects on forest description on a regular basis is the International Co-operative Programme on Assessment and Monitoring of Air Pollution Effects on Forests (ICP Forests).…”
Section: Introductionmentioning
confidence: 99%